An Analysis Of Indirect Illocutionary Acts Used By Bu Tedjo In Tilik Film - Aget Pramana; Dhanu Ario Putra; Lina Tri Astuty (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the indirect illocutionary acts performed by Bu Tedjo in the Indonesian short film Tilik (2020) and to examine their functions within social interactions. This study employed a descriptive qualitative method. The data were collected through observation and documentation by watching the film repeatedly, transcribing the dialogues, identifying Bu Tedjo’s utterances, and classifying the indirect illocutionary acts based on Searle’s (1979) theory. Furthermore, the functions of the illocutionary acts were analyzed using Leech’s (1993) classification, namely competitive, convivial, collaborative, and conflictive. The findings reveal that there are sixteen utterances containing indirect illocutionary acts, which are classified into four types: request (6%), assertion (75%), question (13%), and suggestion (6%). Assertion is the most dominant type, indicating that Bu Tedjo frequently uses indirect language to express opinions, suspicions, and moral judgments. In terms of function, the conflictive function is the most dominant (69%), followed by collaborative (19%), competitive (6%), and convivial (6%). The dominance of conflictive function shows that indirect utterances are mainly used to criticize, accuse, and express suspicion, although they are delivered indirectly to maintain politeness and social harmony. This study concludes that indirect illocutionary acts in Tilik function as pragmatic strategies to negotiate power, influence others, and manage interpersonal relationships within a cultural context that values indirectness and politeness.